Women in Western and Eastern Manichaeism : Selected Papers from the International Conference Les femmes dans le manichéisme occidental et oriental held in Paris, University of Paris Sorbonne, 27-28 June 2014 - Scopello, Madeleine, (Nag Hammadi and Manichaean Studies ;, 2022)
The exceptional place women held in Manichaeism, in everyday life or myth, is the object of this book. Relying on firsthand Manichaean texts in several languages and on polemical sources, as well as on iconography, the various papers analyze aspects of women's social engagement by spreading Mani's doctrine, working to support the community, or corresponding with other Manichaean groups. Topics such as women's relation to the body and elect or hearer status are also investigated. The major role played by female entities in the myth is enlightened through occidental and oriental texts and paintings discovered in Central Asia and China.